Inovasi Schotel Tape di Desa Banjarsari sebagai Strategi Pemberdayaan Masyarakat dan Penciptaan Alternatif Produk Turunan Industri Layak Hilirisasi - Ica Purnamasari; Umu Da'watul Choiro; R. Anggia Listyaningrum; Eka Putri Surya; Alby Aruna; Adinda Marcelliantika (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This article discusses the innovation of Schotel Tape in Banjarsari Village as a strategy for community empowerment and the creation of viable downstream industrial derivative products. This community service program aims to enhance the skills and knowledge of the community in processing tape into high-value-added products. The methodology includes training, mentoring, and program effectiveness evaluation. The results indicate that the Schotel Tape innovation successfully increases community income and creates new business opportunities. Additionally, the program facilitates collaboration among residents and raises awareness of the importance of product diversification. In conclusion, the Schotel Tape innovation provides a positive contribution to community economic empowerment and can serve as a model for the development of other derivative products.